Understanding knowledge and approval for sociopolitical groups: results from the 2023 National Survey of Gun Policy - Rebecca Valek; Julie A. Ward; Vanya Jones; Tim Carey; Cassandra K. Crifasi (Injury Epidemiology)
Abstract Background Increased concerns of political violence in the US have drawn attention to sociopolitical movements across the political spectrum. The 2023 National Survey of Gun Policy sought to characterize approval of these movements and whether gun ownership was associated with this approval. Methods The National Survey of Gun Policy was fielded from 1/4/23 − 2/6/23 among a nationally representative sample of US adults (N = 3,096), including gun owners (n = 1,002). Respondents rated their level of approval for the militia, antifascist (Antifa), white supremacy, Christian nationalist, boogaloo, and anarchist movements. Logistic regression was used to compare differences in movement approval by gun ownership. Results Approval of each movement was relatively low, ranging from 4% for the boogaloo movement to 13% for the Christian nationalist movement. Proportions of respondents that reported lacking knowledge was highest for the boogaloo movement (64%) and lowest for the white supremacy movement (17%); these two movements had similar proportions of approval (4% and 5%, respectively). Significantly larger proportions of gun owners reported both knowledge and approval of any of the six movements compared to non-gun owners, but differences in approval by gun ownership were no longer significant when only comparing those with knowledge of the movements. Conclusions Results indicate low probabilities of knowledge and approval. Moreover, greater knowledge was not accompanied by greater approval (e.g., white supremacy). Gun ownership was associated with movement knowledge, but not with movement approval among those with knowledge. These findings suggest opportunities for more proactive public health messaging to appeal to majority groups to resist movements that may sow division.